THE AUTHORITY OF A NOTARIAL DEED COPY THAT UNDERTAKES CORRECTIONS DUE TO WRITING AND/OR TYPING ERRORS - Fandy Purnama; I Wayan Wesna Astara; Ida Bagus Agung Putra Santika (Journal of Golden Generation Legal Science, 2026)
The ambiguity of the norms in Article 51 of the Law raises issues regarding the validity of copies of corrected deeds and the liability of Notaries towards the parties involved. This study aims to analyze the legal status of the corrected deed copies and the forms of Notaries' responsibility for errors that occur. The research method used is normative juridical legal research with legislative and conceptual approaches, through descriptive qualitative analysis of primary and secondary legal materials. Research findings indicate that corrections to copies of deeds remain valid and equivalent to the deed minutes as long as the errors are administrative in nature and the corrections are made in accordance with regulations, so they do not alter the substance of the deed. However, if corrections are made not in accordance with the UUJN procedures or result in substantial differences with the minutes, then the copy of the deed may be downgraded to a private deed and categorized as a legally defective deed. Notaries are liable in civil, administrative, criminal, and ethical terms, because such negligence constitutes an unlawful act under the concept of liability. In conclusion, corrections to deed copies remain valid as long as they do not change the substance and are carried out according to procedure, while Notaries are obliged to bear legal responsibility for any typing or writing errors arising from their negligence.